Pengaruh Pendapatan, Pekerjaan, dan Pendidikan Terhadap Keputusan Masyarakat Melakukan Pinjaman Online - Abdillah Arif Nasution; Haris Karyadi; Andreas Recki Prasetyo; Afni Yeni; Eva Yuniarti Utami (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of technology from time to time is growing rapidly, one of which is in the financial sector. This development is marked by the emergence of financial technology in the era of modernization. Online loans are a form of financial technology service which is a money lending service to make it easier for people to borrow money without any hassle like in conventional banks. This study uses a quantitative research type. This study aims to determine the effect of income, employment, and education on people's decisions to make online loans. The population of this study is people who have used online loans. The results of this study found that income, employment and education influence people's decisions to make online loans.